2009
DOI: 10.1111/j.1365-2427.2009.02207.x
|View full text |Cite
|
Sign up to set email alerts
|

Linking landscape‐level change to habitat quality: an evaluation of restoration actions on the freshwater habitat of spring‐run Chinook salmon

Abstract: 1. Conservation planning is often hampered by the lack of causal quantitative links between landscape characteristics, restoration actions and habitat conditions that impact the status of imperilled species. Here we present a first step toward linking actions on the landscape to the population status of endangered stream-type Chinook salmon (Oncorhynchus tshawytscha). 2. We developed relationships between land use, landscape characteristics and freshwater habitat of spring Chinook salmon in the Wenatchee River… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 59 publications
0
24
0
1
Order By: Relevance
“…Several studies have identified similar immutable predictors as primary drivers of sediments or geomorphic conditions describing stream size (e.g. pool volume or depth) Burnett et al , ; Jorgensen et al , ). Much of the current research has shown that sediment dynamics in streams is sensitive to land use and management (Wood and Armitage, ; Kaufmann et al , ; Larsen et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified similar immutable predictors as primary drivers of sediments or geomorphic conditions describing stream size (e.g. pool volume or depth) Burnett et al , ; Jorgensen et al , ). Much of the current research has shown that sediment dynamics in streams is sensitive to land use and management (Wood and Armitage, ; Kaufmann et al , ; Larsen et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that precipitation is an overarching driver of the chemical, physical, and biological processes contained within the conceptual model (Feminella, 1996;Monk et al, 2008;Jorgensen et al, 2009). Essentially, we are assuming that precipitation moderates the entire casual graph.…”
Section: Bayesian Parameter Estimationmentioning
confidence: 99%
“…Wenatchee River Basin hydrology is dominated by snowmelt with the highest flows occurring between May and July and the lowest in August and September. See Jorgensen et al (2009) for a more detailed description of the basin. We modeled all of the major salmon-producing tributaries of the Wenatchee River, including the Chiwawa, White, and Little Wenatchee rivers, as well as Nason Creek and the upper reaches of the mainstem Wenatchee River.…”
Section: Populationmentioning
confidence: 99%
“…Landscape attributes included total forest cover, riparian forest cover, road density, stream channel slope, elevation, precipitation, and drainage area. See Jorgensen et al (2009) for additional details of the landscape models. For this analysis, we expanded on our previous work in Jorgensen et al (2009) by re-examining the landscape models to determine the key landscape variables that could be targets for action to ameliorate climate impacts on stream habitat.…”
Section: Climate Hydrology Landscapementioning
confidence: 99%
See 1 more Smart Citation